Sub-central Governments and the Economic Crisis Impact and Policy Responses - Blöchliger, Hansjörg (OECD Economics Department Working Papers, 2010)
The world is recovering from the worst crisis since the Great Depression, leaving a strong and lasting impact on Member countries' public finances. This paper analyses how sub-central governments (SCG) are affected and how fiscal policy has reacted in the first months after the outbreak of the crisis. In general and in line with earlier downturns, SCG's public finance appear to be less affected than central governments. However, SCGs suffer from a scissors effect of higher spending and lower tax revenue, specially those with a volatile tax base and large social welfare responsibilities. While some SCGs were conducting their own stimulus plans, others cut expenditures and raised taxes, potentially undermining national government's recovery programmes. Most national governments are helping SCGs to cope with the crisis, by disbursing additional grants and supporting investment programmes, by easing centrally-imposed fiscal rules, lifting borrowing constraints or by temporarily raising the sub-central tax share. The crisis also showed the need for better coordination in intergovernmental fiscal relations, both for more macroeconomic coherence and for efficiency in public service delivery. Several countries are creating or reinvigorating their institutions for managing relations across levels of government